Marketing of PAUD Services in The Pandemic Period in PG-TK Pelangi Ceria (Based on Sementation, Positioning, and Targeting) - Adelia Miranti Sidiq; Na'imah Na'imah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
This pandemic period makes educational institutions work even harder in marketing educational services, and each institution will make marketing management using a variety of methods, as we know that in this case, early childhood education institutions are one of the institutions that have tough competition between one institution and one institution. another. Therefore, school institutions must show clear and ideal quality of their institutions. The main problem in this research is to find out the marketing of educational services in Kindergarten Pelangi Ceria. This research aims to explore and convey new information related to the marketing of educational services. The research method used is to use qualitative research methods in which data collected by observation, interviews, and documentation. Then the data analysis technique used data analysis, data presentation, and drawing conclusions by triangulating the data. The results of this study indicate that the PG-TK Pelangi Ceria school institution indirectly implements PAUD service marketing management by determining market segmentation, positioning, and targeting. Even before the pandemic, the PG-TK Pelangi Ceria institutions had marketed their educational services through digital or via social media, so that the PG-TK Pelangi Ceria remained highly competitive among PAUD institutions around the Delta Sari area.